Systematic identification and characterization of long noncoding RNAs (lncRNAs) during Aedes albopictus development - Wenjuan Liu; Peng Cheng; Kexin Zhang; Maoqing Gong; Zhong Zhang; Ruiling Zhang (Public Library of Science (PLoS), 2022)
Background Aedes albopictus originated in the tropical forests of Southeast Asia and can currently be found on all continents. As one of the main arboviral vectors, the control of Ae. albopictus requires novel strategies, informed by a deep knowledge of its biology. Little is known regarding mosquito long noncoding RNAs (lncRNAs), which are transcripts longer than 200 nucleotides that lack protein-coding potential and have roles in developmental regulation. Results Based on RNA-seq data from five developmental time points, eggs, early larvae, late larvae, pupae, and adults (female and male) of Ae. albopictus, 21,414 lncRNAs were characterized in this study. Differential expression analysis revealed that lncRNAs exhibited developmental stage specificity. The expression of most lncRNAs was upregulated at the onset of metamorphosis developmental stages. More differentially expressed lncRNAs were observed between eggs and early larvae. Weighted gene co-expression network analysis (WGCNA) further confirmed that the expression patterns of lncRNAs were obviously correlated with specific developmental time points. Functional annotation using co-expression analysis revealed that lncRNAs may be involved in the regulation of metamorphic developmental transitions of Ae. albopictus. The hub lncRNAs and hub gene clusters were identified for each module that were highly associated with specific developmental time points. Conclusions The results of this study will facilitate future researches to elucidate the regulatory mechanisms of lncRNAs in the development of Ae. albopictus and utilize lncRNAs to assist with mosquito control. Author summary Aedes albopictus is an invasive vector mosquito associated with substantial public health concerns. It is a vector of dengue, chikungunya, and Zika viruses. High levels of ecological and physiological plasticity promote rapid global invasion. In the absence of effective vaccines or specific antiviral drugs for the majority of arbovirus diseases, vector control is based mostly on chemical insecticides. However, the extensive and intensive use of chemical insecticides for mosquito control has caused several environmental and human health concerns. As holometabolous insects, mosquitoes undergo considerable structural and functional remodeling during the metamorphosis. Long noncoding RNAs (lncRNAs) have been reported to play roles in developmental regulation. To investigate the expression profiles of lncRNAs across the life cycle of Ae. albopictus, five developmental time points, eggs, early larvae, late larvae, pupae, and adults (female and male), covering all developmental stages were included in this study. Differences in lncRNA expression patterns and hub lncRNAs that were highly associated with specific developmental time points were identified. Hub lncRNAs could be used as targets to block the metamorphic process and facilitate the development of efficient and sustainable mosquito control strategies.